Remote temperature monitoring and analysis of thermoforming process - Muhammad Faiz, Ab. Rahim (2015)
Web-based Graphical User Interface for Manufacturing Process is one of the latest features to be implemented on most industry's machine recently due to availability of wide Internet network. The concept of connecting object to Internet network has been introduced by Kevin Ashton under the term of “Internet of Thing”. In this project, temperature monitoring devices for thermoforming machine heating section is being design and builds to measure temperature respond of radiation and convection heat transfer using thermocouples. The focuses on this project is to produce low cost data acquisition system using the spark core microcontroller that can display and record data remotely. It was found that using this system it enables far distance monitoring operation yet only suitable for certain type of process that perform at low response.